Developmental Perturbation Induced by Maternal Asthma during Pregnancy: The Short- and Long-Term Impacts on Offspring - Vicki L. Clifton; Michael Davies; Vivienne Moore; Ian M. R. Wright; Zainab Ali; Nicolette A. Hodyl (Journal of Pregnancy)
Maternal asthma is a common disease to complicate human pregnancy. Epidemiological studies have identified that asthma during pregnancy increases the risk of a number of poor outcomes for the neonate including growth restriction, lower birthweight, preterm delivery, neonatal resuscitation, and stillbirth. Asthma therefore represents a significant health burden to society and could have an impact on the lifelong health of the children of women with asthma. Our research has identified that maternal asthma in pregnancy induces placental dysfunction and developmental perturbation in the fetus in a sex specific manner. These alterations in development could increase the risk of metabolic disease in adulthood of children of asthmatic mothers, especially females. In this paper, we will discuss the evidence currently available that supports the hypothesis that children of mothers with asthma may be at risk of lifelong health complications which include diabetes and hypertension.